An Appraisal of Vendor Managed Inventory Strategy in Mining Operations, the Case of Gold Fields Ghana Ltd. - Djan, Joseph Danso (2011)
A thesis submitted to the School of Business, Kwame Nkrumah University of Science and Technology, Kumasi —Ghana in partial fulfillment of the requirement for the Degree of Master of Business Administration,